Maximal Arbitrage - Klaus Schürger (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
Let S=(S_t), t=0,1,...,T (T being finite), be an adapted R^d-valued process. Each component process of S might be interpreted as the price process of a certain security. A trading strategy H=(H_t), t= 1,...,T, is a predictable R^d-valued process. A strategy H is called extreme if it represents a maximal arbitrage opportunity. By this we mean that H generates at time T a nonnegative portfolio value which is positive with maximal probability. Let F^e denote the set of all states of the world at which the portfolio value at time T, generated by an extreme strategy (which is shown to exist), is equal to zero. We characterize those subsets of F^e, on which no arbitrage opportunities exist.
Keywords: G12; D40; G13; 330; Arbitrage; martingale measure; Arbitrage Pricing; Martingale; Theorie